Is a gender revolution possible in Poland? Analysis of the potential for changes in the perspective of the theory of Goldscheider, Bernhardt and Lappegard = Czy w Polsce możliwa jest rewolucja płci? Analiza potencjału zmian w perspektywie teorii F. K. Goldscheider, E. Bernhard I T. Lappegard - Juszczyk-Frelkiewicz, Katarzyna; Paprzycka, Emilia (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The purpose of the article is to analyse the changes in private life and gender relationships in Poland after 1989 in the context of the Polish society?s potential for the second stage of the gender revolution. The authors look at the changes from the perspective of the gender revolution theory as defined by F. K. Goldscheider, E. Bernhard and T. Lappegard. The changes were analysed in the context of the concept of the second demographic transition by Van de Ka. They were treated as conditions for further transformations in the relationships between men and women. The results show that in Poland the gender revolution stopped at the first stage.
Keywords: gender revolution; Second Demografic Transition; division ofhousehold duties; marriage and family life; rewolucja płci; drugie przejście demograficzne; życie małżeńsko-rodzinne; podział obowiązków domowych